Improved results on synchronisation of delayed complex dynamical networks via sampled-data control. Issue 6 (26th April 2018) - Zeng, Deqiang; Zhang, Ruimei; Liu, Xinzhi; Zhong, Shouming; Shi, Kaibo
ABSTRACT: This paper focuses on the synchronisation problem of delayed complex dynamical networks via sampled-data control. A novel input-delay-dependent Lyapunov–Krasovskii functional (LKF) is constructed for the first time, which can make full use of the information on the input delay. To strengthen the combinations of the vectors in the resulting augmented vector, a new zero value equality is founded. Based on the input-delay-dependent LKF and zero value equality, synchronisation criteria are established. In comparison with some existing synchronisation criteria, the criteria in this paper are less conservative. The desired sampled-data controller is designed by solving a set of linear matrix inequalities. Finally, numerical examples are given to demonstrate the superiorities of proposed results.